The Role, Significance, and Association of MicroRNA-10a/b in Physiology of Cancer - Elgeshy, Khaled M.; Abdel Wahab, Abdel Hady A. (MicroRNA, 2022)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate the translation of mRNA and protein, mainly at the posttranscriptional level. Global expression profiling of miRNAs has demonstrated a broad spectrum of aberrations that correlated with several diseases, and miRNA- 10a and miRNA-10b were the first examined miRNAs to be involved in abnormal activities upon dysregulation, including many types of cancers and progressive diseases. It is expected that the same miRNAs behave inconsistently within different types of cancer. This review aims to provide a set of information about our updated understanding of miRNA-10a and miRNA-10b and their clinical significance, molecular targets, current research gaps, and possible future applications of such potent regulators.
Keywords: diagnosis